Praktik Skeptisisme Profesional Auditor Internal dalam Mengungkap Fraud: Studi Kualitatif pada PT. Abhava Delapan Belas - Firly Husniyatul 'Adawiyah; Ajeng Tita Nawangsari (Indo Publishing, 2025)
This study aims to analyze the practice of professional skepticism applied by internal auditors in their efforts to detect fraud within corporate environments. Using a qualitative approach with a case study method, the research involved interviews with three key informants who are senior internal auditors with significant experience in audit assignments. The findings reveal that although the informants understand professional skepticism as a critical and questioning mindset that resists easy acceptance, its implementation faces various practical challenges, such as time pressure, interpersonal relationships with auditees, and the availability of evidence. These findings highlight the gap between theory and practice, where internal auditors often need to balance the ideal skeptical attitude with operational realities. This study provides practical implications for audit management and professional standard setters to strengthen the practice of professional skepticism through training and institutional support.